Implementation Of Perceptron Algorithm For Logic Gates Using ANN - et. al., Chowdhari M I, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Biological/organic neurons ar the main components of human brain. Neuron processes and sends information to other neuron by sending electrical signals. Artificial neurons are inspired by biological neurons. These artificial neurons are interconnected to form artificial neural networks. This neural network’s structure helps to make computation faster for certain tasks hence making it suitable for implementation in VLSI technology. Then the Logic gates is implemented using feed forward network and the design is realized using Verilog HDL.